Receptor protein tyrosine phosphatase alpha activates pp60c-src and is involved in neuronal differentiation. - den Hertog, J (1993)
Here we report that protein tyrosine phosphatases (PTPases), like their enzymatic counterpart the protein tyrosine kinases, can play an important role in cell differentiation. Expression of the transmembrane PTPase receptor protein tyrosine phosphatase alpha (RPTP alpha) is transiently enhanced during neuronal differentiation of embryonal carcinoma (EC) and neuroblastoma cells. Retinoic acid induces wild type P19 cells to differentiate into endoderm- and mesoderm-like cells. By contrast, retinoic acid treatment leads to neuronal differentiation of P19 cells, ectopically expressing functional RPTP alpha, as illustrated by their ability to generate action potentials. Endogenous pp60c-src kinase activity is enhanced in the RPTP alpha-transfected cells, which may be due to direct dephosphorylation of the regulatory Tyr residue at position 527 in pp60c-src by RPTP alpha. Our results demonstrate that RPTP alpha is involved in neuronal differentiation and imply a role for pp60c-src in the differentiation process.